Salat Sepanjang Sejarah Para Anbiya - Abd. Ghani, Anisah (Jurnal Usuluddin, 1997)
The article analyses the saint, which has being implemented for a long time ago. The differences between salat in the period of holy Prophet Muhammad (p. b. u. h.) and the period of previous Messengers are basically from time, methods and the number of Rakaat.